GAS ELECTRIC VALVE DESIGN - Kartika, Kartika; Rezki Setiawan, Ahmad (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
In this era of globalization, science and technology has developed rapidly, especially in the industrial world. As for science and technology that is beneficial to industry, namely for components of the production process, one of which is Valve control. This technology is used to modify the fluid flow or pressure rate in a process system by using power for its operation. The application of this control valve is used to control a pressure rate or quantity, such as the amount of oxygen gas content (O₂) and carbon dioxide (CO₂) in fruit and vegetable plants. In the research that has been carried out on the carbon dioxide (CO₂) process using a porous fiber membrane contactor, the gas model is absorbed in a pure state at cold room temperature. In this study, it is still an obstacle when applied in the field because there are many factors that have not been taken into account, so in an effort to control the wasted gas, an electric gas valve control system device is needed which is designed to determine the value of wasted gas. This system is designed with valve components, servo motors, solenoid valves, Arduino uno, and relays, where all these components are built and programmed with Arduino uno microcontroller. The results of the test are carried out to determine the level of accuracy of each input to the control valve and to determine the value of the gas wasted at the degree of opening of the valve. The test results on the ten forms of angular movement are when the valve works and opens at a movement angle of 0° to the movement, the valve opens at 0%. When the valve works and opens at an angle of movement of 10° to rotation, the valve opens by 11.1%, and when the valve works and opens at an angle of movement of 20° to 80° to the movement, the valve opens by 22.2% to by 88.8%, then when the valve works and opens at an angle of movement of 90° to the movement, the valve opens by 100% or fully opens. The benefits of this research in the performance process of production technology in industry are to meet consumer demand by producing safe, minimally processed, additive-free, and stable quality food.